A light microscopic study of placentae in eclamptic mothers at term - Meyur, Rudradev; Sadhu, Anirban; Mondal, Hironmoy; Khanra, Santanu Kumar (International Journal of Research in Medical Sciences, 2017)
Background: Eclampsia is one of the leading causes of maternal and consequent foetal mortality in India. Studies on the histology of eclampsia are relatively uncommon, more so in the eastern region of India. The present study therefore is an attempt to analyse the changes which occur in placentae of eclamptic mothers with the help of light microscope as it is considered to be the epicentre of the disease. These findings are useful to understand the pathology of the killer disease and improve morbidity and mortality. Methods: 60 cases were selected for the study. 30 were non-eclamptic and 30 were eclamptic. Abnormalities in blood vessels, villi and basement membrane of placentae were searched for after routine H and E staining. Results: Eclamptic cases recorded with higher incidences of fibrinoid necrosis of villi, cytotrophoblastic proliferation, increased syncytial knots, hypo vascular villi and thickening of basement membrane. Non-eclamptic cases recorded only fibrinoid necrosis. Other features were not observed in the latter cases. Conclusions: Light microscopic changes observed in eclamptic placentae may contribute to the pathogenesis of the condition and serve as the baseline for further studies.